Effect of solids residence time on dynamic responses in chemical P removal. (28th January 2019) - Conidi, Daniela; Parker, Wayne J.; Smith, Scott
Abstract: The impact of solids residence time (SRT) on the dynamics of phosphorus (P) removal by hydrous ferric oxide (HFO) floc was characterized through experimental and modeling studies. Three abiotic process conditions were considered in systems operated over a range of SRTs ( 3 to 27 days): uptake in sequencing batch reactors (SBRs) under (a) constant and (b) dynamic P loading conditions, and (c) uptake in batch sorption tests with preformed HFO solids. P removal under all conditions was characterized by an initial period of fast removal followed by a period of slower removal until pseudo‐equilibrium was reached. The initial removal rate increased with increasing P concentrations and was attributed to a larger concentration gradient between soluble‐ and adsorbed‐phase concentrations. A kinetic model was developed and found to describe the dynamic behavior of P adsorption onto HFO floc under all conditions tested. A consistent mass transfer rate coefficient ( k ) was found to describe mass transfer over a range of SRTs for low initial P concentrations. At elevated SRTs (23–27 days) and elevated influent P concentrations, k values were found to deviate from those estimated at reduced SRTs. Differences in process mixing conditions were reflected in the estimated rate coefficients ( k ). Integration of the kinetic model with existing equilibrium models in wastewater process simulators will improve the ability to predict P uptake onto HFO floc under dynamic loading conditions in water resource recovery facilities. Models that consider the kinetics of P uptake will be particularly relevant for facilities that are required to achieve ultralow P concentrations. Practitioner points: This work provides a kinetic model that can be integrated with existing equilibrium models in wastewater process simulators to improve the ability to predict P uptake onto HFO floc under dynamic loading conditions. This research can be used to assist WRRFs to achieve ultralow effluent P requirements.